International tax planning: Current state of knowledge - Vít Jedlička (European Financial and Accounting Journal, 2017)
Globalisation affects the behaviour of managers of companies and brings many new possibilities in management. These changes affect activities related to tax optimization and they can be collectively called as international tax planning. This paper monitors current situation of tax planning activities and its aim is to present a current state of knowledge. It contains data showing high frequency of tax planning activities. There are briefly outlined ways of international tax optimization and attitude of organisations to the tax planning of multinationals corporations. Significant part of this paper is devoted to the overview of literature, which deals with measuring international tax optimization. There are several attitudes in selected studies that can be also used (with adaptation to the different data) for monitoring of situation in the Czech Republic. Overall, the most attitudes use applications of effective tax rate and this rate, which is for every country and corporation different, is a key factor for tax planning decision-making.
Keywords: H25; M29; 650; International tax planning; Profit shifting; Tax optimization